Способ получения на поверхности ленты-фольги из ниобий-титанового сплава изолирующего оксидного покрытия - Образцов С. В. Сергей Викторович; Ивлеева А. М. Айгуль Муратовна; Орлов А. А. Алексей Алексеевич; Исмагулова А. Д. Айгуль Джамаловна
опубл. 10.01.12